Source–sink relationships during early crop development influence earliness of sugar accumulation in sugarcane - Saez, Julio Victor (2019)
In subtropical environments where sugarcane (Saccharum spp.) crops are frequently limited by the duration of the growth cycle, earliness in maturity is a key genotypic trait. Using the concept of source–sink relationships, we hypothesised that earliness is controlled by the dynamics of tillering (DT), which define sink strength early in the growth cycle. Five modern commercial sugarcane genotypes with similar sucrose yields and varying degrees of earliness in ripening were grown in the field over three years and their DT, dynamics of sucrose accumulation (DS), and source–sink relationships over time were characterised. Canonical correlations and principal components analysis revealed that DT explained 68% of the total variance in DS. Early ripening genotypes exhibited the shortest thermal time to the end of tiller mortality (θTilmort), the lowest tiller survival and millable tiller number, and greatest sugar content at θTilmort (Sconc,Tilmort). The rate and duration of the sucrose accumulation phase did not explain the genotypic variation either in final sugar content or in earliness when considered in isolation without taking into account the effect of Sconc,Tilmort. In the set of genotypes examined, the variation in final sucrose yield was most explained by the variation in stalk number. We conclude that the dynamics of tiller appearance and senescence modified the early source–sink relationships and thus determined the differential sucrose contents around θTilmort and the earliness of maximal sugar accumulation. θTilmort, which was closely associated with the 14-leaf phenological stage, emerged as a candidate trait to screen for genotypic variation in early ripening, crop cycle duration, and yield.